App Coronavírus-SUS: An Evalution Using the Ergonomic Criteria of Usability - Milczuk, Samuel Stephan; Pereira, Roberto; Boscarioli, Clodis (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2020)
The Ergonomic Criteria for Usability by Christian Bastien and Dominique Scapin are a set of ergonomic standards that graphic user interface must present. Popular in the 90s, the criteria are not aimed at mobile devices, motivating this research to apply these criteria to see their suitability for new scenarios of hardware and software. As a firts step towards revisiting the Ergonomic Criteria, we present results and discussions from an evaluation activity where the criteria were applied to evaluate the Coronavirus-SUS, an application developed to inform Brazilian population about the COVID-19 pandemic situation. Because the application’s target audience is the entire Brazilian population, many different issues can be experienced and must be considered. Results reveal several critical problems that may affect the application understanding and usage, and suggest the criteria are able to support usability evaluation in mobile contexts, although a need for revisiting and updating the criteria was identified.